Around the Backside: Productive Disbelief in Burning Vision - Fletcher, Alana (Theatre Research in Canada / Recherches théâtrales au Canada, 2016)
The work of Vancouver-based Métis playwright Marie Clements has often been commended for its emphasis on the connections that inhere among people and places, times and spaces. The time-space conversations of Burning Vision , one of the most spatially and temporally diverse of Clements’s works, have thus far been explained in terms of their ecological and indigenizing effects. While revelations of connectivity and windows opened onto alternate conceptions of spatio-temporality are significant results of the intercultural moments where Clements brings discrete times and places into conversation, it is also useful to acknowledge another, more immediate result of such dialogues: audience confusion, alienation, and disbelief. Such confusion points to a significant but as-yet unaddressed aspect of the Burning Vision : the way the play’s materiality works against its fiction, impeding audience immersion in the story unfolded. This article draws out this conflict through a phenomenological approach that illuminates how the refusal of the work’s material reality to disappear behind its fiction—to slip around the backside of the frontside illusion—prompts a productive kind of disbelief that structurally underlines the work’s arguments for interconnectedness.